Aptamer-based determination of ATP by using a functionalized impedimetric nanosensor and mediation by a triangular junction transducer - Gopinath S.C.B.; Perumal V.; Balakrishnan S.R.; Md Arshad M.K.; Lakshmipriya T.; Haarindraprasad R.; Hashim U. (Springer-Verlag Wien, 2024)
Indexed by SCOPUS